Construction of a novel catalysis system for clean and efficient preparation of Baohuoside I from Icariin based on biphase enzymatic hydrolysis. (1st January 2018) - Shen, Yuping; Wang, Haiyan; Lu, Yi; Xu, Lili; Yin, Huawu; Tam, James P.; Yang, Huan; Jia, Xiaobin
Abstract: Baohuoside I has better in vivo bioactivities than Icariin. Its preparation methods, such as acid hydrolysis, are of low efficiency, with undesirable byproducts. The objective of this study was to establish a novel catalysis system for its clean and efficient preparation via biphase enzymatic hydrolysis. β -glucosidase was selected from five commercial enzymes due to the best catalysis performance. After optimization of conditions, a biphase system was constructed with EtOAc and HAc-NaAc buffer (pH 4.5) (5:1, v/v ) containing Icariin/ β -glucosidase (3.2:1, w/w ), and hydrolysis was performed at 60 °C for 2 h. Consequently, the conversion rate of Icariin was 99.92 ± 0.11% (n = 3), and the processing capacity in the system was increased from 20 mg/mL to 50 mg/mL, 2.5 times that of conventional enzymatic hydrolysis, meanwhile the procedure was much simplified. Additionally, complete hydrolysis with conversion rate at 99.14% had been achieved after the enzyme solution was used twice. The newly proposed strategy is a clean and efficient approach for the preparation of Baohuoside I and also a promising technology for producing secondary glycosides or aglycones. Graphical abstract: Image Highlights: Hydrolysis of Icariin and extraction of Baohuoside I, were accomplished by a clean and efficient approach. A novel catalysis system was constructed based on biphase enzymatic hydrolysis for the first time. The processing capacity of the novel system was determined to be 2.5 times that of conventional enzymatic hydrolysis. An up to 85% conversion rate was achieved after the enzyme solution was used three times.